Metformin use and the Risk of Gastrointestinal Malignancies in Diabetic Populations: A Meta-Analysis - Gil Hevroni; Samara Skwiersky; Angelina Zhyvotovska; Samy I McFarlane (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
Background: Metformin use has been associated with a decreased risk of cancer and improvement in overall cancer survival rates. However, scant data available regarding metformin's role in the risk of Gastrointestinal (GI) malignancies in patients with type II diabetes. Our study aimed to conduct a meta-analysis to evaluate the association of metformin use and GI cancer risk.  Methods: We conducted electronic search by two independent investigators using the PubMed and Cochrane library databases. Studies were assessed for design and quality, and a meta-analysis was conducted to quantify the effect of metformin on the odds of developing specific GI malignancies. The final papers that met our prespecified inclusion criteria included 4 case-control studies that address metformin's effect on pancreatic cancer, and 4 case-control studies that address metformin's effect on colorectal cancer in patients with type II DM.  Results: Of 2258 articles screened, 8 eligible studies were identified comprising 483,561 participants diagnosed with DM. Our analysis showed that metformin use was not associated with a significant effect on the odds of developing pancreatic cancer (OR .98; 95% CI 0.82-1.17, P=0. 83). Metformin use was associated with significantly lower odds of having Colorectal Cancer (CRC); (OR 0.84; 95% CI 0.81-0.87, p < 0.01). Sufficient data were not available to conduct analyses on the impact of metformin dose and duration. Conclusion: Our findings suggest that metformin could be a useful neoadjuvant agent for CRC cancer and as a possible preventive therapy for other inflammatory conditions related to colorectal pathologies such as adenomatous polyps and inflammatory bowel disease. Further research is warranted to elucidate the role of metformin on the risk of developing pancreatic cancer, given the complex nature of the organ's regulation on insulin production.